Correlation between fatty acyl composition in neutral and polar lipids and enzyme activities from various tissues of calcium-deficient rats - Marra, Carlos Alberto (2002)
In this study we investigated the changes induced by feeding rats a calcium-deficient diet (0.5 g Ca/kg diet) during 65 d after weaning. Phospholipase A2, acyl-Co synthetase and FA Δ9-, Δ6-, and Δ5-desaturase activities were also determined. Calcium deficiency evoked a general alteration in the quality and proportion of the FA chains acylated to neutral and polar lipids from liver, lungs, spleen, brain, kidneys, fat, articular cartilage, erythrocyte ghosts, and plasmas, characterized by an increment of saturated FA and a significant depletion of polyunsaturated acids derived from linoleate and α-linolenate. Several interlipid and lipid/protein relationships were also modified in microsomes from calcium-deprived rats, with a concomitant reduction in the rotational mobility of the probe diphenylhexatriene. Phospholipase A2 and acyl-CoA synthetase activities were also decreased and increased, respectively, in some tissues from calcium-deficient rats, whereas Δ9-, Δ6- and Δ5-desaturases were significantly depressed. We conclude that changes in tissue fatty acyl composition evoked by calcium deprivation are due to alterations in the acylation/deacylation cycles via inhibition of the phospholipase A2. These changes were reflected in the physicochemical properties of the membranes, which in turn inhibits desaturase activities. A possible failure in the transcriptional rate for desaturase-mRNA was also discussed.